Waterfowl in north-east Asia - Kistchinski, A A (Wildfowl, 1973)
The distribution of waterfowl on breeding, moulting, migration, and wintering grounds in north-east Asia is described and the main areas of concentration indicated. Trends in the waterfowl populations are outlined. The situation in the arctic tundra is quite satisfactory for the ’sea-wintering’ Long-tailed Duck Clangula hyemalis and eiders which migrate along arctic coasts, as well as probably for the Snow Goose Anser caerulescens, Emperor Goose Anser canagicus and the eastern populations of Brent Branta bernicla. The status of the White-fronted Goose Anser albifrons and especially of Yakutian populations of Brent is unfavourable. Waterfowl populations breeding in southern tundras, forest-tundras and northern thin-forest taiga, are still highly productive in places, but their total numbers have strongly decreased in the last 20-25 years. The main cause seems to be overhunting and habitat deterioration on migration and wintering grounds. On Sakhalin and Kamtchatka breeding waterfowl are no longer numerous, but birds are abundant on migration. In the lower Amur basin, waterfowl stocks have strongly diminished due to habitat degradation, overharvesting and disturbance on breeding grounds, migration routes and probably on winter ranges as well. Brent Geese, Baikal Teal Anas formosa and some rare species have suffered especially. More studies are necessary, as well as urgent protective measures (including international ones) directed to the protection of habitats and creation of reserves.